2017
DOI: 10.1109/taffc.2016.2582490
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load Measurement in a Virtual Reality-Based Driving System for Autism Intervention

Abstract: Autism Spectrum Disorder (ASD) is a highly prevalent neurodevelopmental disorder with enormous individual and social cost. In this paper, a novel virtual reality (VR)-based driving system was introduced to teach driving skills to adolescents with ASD. This driving system is capable of gathering eye gaze, electroencephalography, and peripheral physiology data in addition to driving performance data. The objective of this paper is to fuse multimodal information to measure cognitive load during driving such that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 53 publications
1
62
0
1
Order By: Relevance
“…Nevertheless, in the long run, obtaining responses through EEG has the potential to develop brain-computer interfaces to improve social skills of individuals with ASD [39]. EEG data were also collected in [141][142][143][144]. In [145], Ozcan et al reported a design for wearable companion toys in which biosensors can be embedded to measure the participant's physiological and emotional state.…”
Section: Physiological Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in the long run, obtaining responses through EEG has the potential to develop brain-computer interfaces to improve social skills of individuals with ASD [39]. EEG data were also collected in [141][142][143][144]. In [145], Ozcan et al reported a design for wearable companion toys in which biosensors can be embedded to measure the participant's physiological and emotional state.…”
Section: Physiological Data Collectionmentioning
confidence: 99%
“…In addition to eye gaze, we have seen studies that employ various methods to obtain user feedback for adaptive control of a treatment/education program, including facial expression, head orientation, human gesture tracking, and physiological data collection [135,136,141,143,146,151].…”
Section: Automatic Adaption Of Programsmentioning
confidence: 99%
“…The β activity corresponds to the frequency band [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz. It is present on both sides of the brain symmetrically.…”
Section: Betamentioning
confidence: 99%
“…Lin et al [30] proposed to monitor driving performance, that is, the driver's ability to maintain the vehicle in the middle of the road, using a linear regression model on a two-channel EEG. When the model is driven and tested on the same session, they get a correlation of r = 0.88 between their model and driving performance.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation